The double posteromedial portals endoscopy for posterior ankle impingement syndrome in athletes - Nicola Maffulli; Rocco Aicale; Filippo Migliorini; WAGNER, EMILIO; Amol Saxena; Francesco Oliva (My University, 2022)
Abstract Background Posterior ankle impingement syndrome (PAIS) may result from flexor hallucis longus tendinopathy, compression of the posterior process of the talus from the presence of an os trigonum, soft-tissue impingement, or a combination of these. Posterior extra-articular endoscopy performed with the patient supine through the double posteromedial portals, with excision of adhesions, excision of the posterior process of the talus or an os trigonum, and decompression of the tendon of the flexor hallucis longus (FHL), can be used in athletes with PAIS. Methods Thirty-four athletes with PAIS in whom conservative management had failed underwent posterior ankle endoscopy in the supine position using the double posteromedial portals. The patients were assessed pre- and postoperatively using the American Orthopaedic Foot and Ankle Society hindfoot scale score, the Tegner scale, and the simple visual analogue scale. Time of surgery, return to sports, patient satisfaction, and complications were recorded and analysed. The average length of postoperative follow-up was 26.7 ± 12.6 (range 24 to 72) months. Results The mean Tegner activity scale score improved to 9 ± 0.2 postoperatively (p < 0.05), while the mean American Orthopaedic Foot and Ankle Society scale score improved to 96 ± 5.1 (range 87 to 100) postoperatively, with 29 of 34 patients (85.3%) achieving a perfect score of 100 (p < 0.05). The mean time to return to sports was 8.7 ± 0.7 (range 8 to 10) weeks. The complication rate was low, with no superficial wound infections or venous thromboembolism events; only two patients (5.9%) reported pain and tenderness by 3 months after the index procedure. Conclusion Posterior ankle endoscopy for the resection of a posterior process of the talus or an os trigonum and decompression of the tendon of FHL is safe and allows excellent outcomes with low morbidity in athletes with PAIS.
Keywords: os trigonum; excision; diagnosis; dancers; ankle; arthroscopy; athletes; endoscopy; humans; joint diseases; syndrome; adolescent; adult; american orthopedic foot and ankle society ankle hindfoot score; article; athlete; clinical article; clinical outcome; conservative treatment; controlled study; double posteromedial portal; endoscopy; female; follow up; human; limb disease; male; patient satisfaction; postoperative care; postoperative pain; preoperative evaluation; prospective study; return to sport; supine position; surgical technique; talus; tegner activity score; time to treatment; treatment failure; visual analog scale; ankle; arthropathy; arthroscopy; athlete; endoscopy; procedures; syndrome